Comparative Study of Diagnostic Efficacy of Single Phase-Computed Tomography Pulmonary Angiography and Dual Phase-Computed Tomography Pulmonary Angiography in the Diagnosis of Pulmonary Embolism - Guan, Xuechun; Lan, Qiaoqing; Liang, Yi; Ke, Honghong; Chen, Siqi; Long, Liling (Frontiers in Cardiovascular Medicine, 2022)
Objective: We compared the efficacy of single phase-computed tomography pulmonary angiography (SP-CTPA) and dual phase-computed tomography pulmonary angiography (DP-CTPA) for the diagnosis of pulmonary embolism (PE). Methods: We recruited 1019 consecutive patients (359 with PE) who underwent DP-CTPA (phase I: pulmonary artery phase; phase II: aortic phase) for suspected PE between January and October 2021. Phase I of DP-CTPA was used as SP-CTPA, and the final clinical diagnosis (FCD) was used as the gold standard. The diagnostic ability of these two methods was assessed based on the area under the curve (AUC) values. Results: 352 cases of PE were detected by both methods. Using SP-CTPA, 142 cases [13 pulmonary insufficiency artifacts (PIA) and 129 systemic-pulmonary shunt artifacts (S-PSA)] were false-positive. No false-positive was found with DP-CTPA. The diagnostic efficacy of DP-CTPA (AUC=0.990; sensitivity: 98.10%; specificity: 100.00%) was better than that of SP-CTPA (AUC=0.883; sensitivity: 98.10%; specificity: 78.50%). According to FCD, the positive results of SP-CTPA were divided into PIA, S-PSA, and true-positive (TPSP-CTPA) groups, and pairwise comparisons were performed. The bronchiectasis and hemoptysis rate in S-PSA group was higher than that in PIA and TP groups (P<0.05), and the pulmonary hypertension (PH) rate in PIA group was higher than that in S-PSA and TP groups (P<0.05). Conclusion: The diagnostic efficiency of DP-CTPA for the diagnosis of PE was relatively high. SP-CTPA may misdiagnose PIA (common in patients with PH) and S-PSA (common in patients with bronchiectasis and hemoptysis) as PE.